2020
DOI: 10.17509/jpki.v6i2.30086
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Violence Againts Women during the COVID-19 Pandemic: A Systematic Review

Abstract: Violence against women is one of the human rights solutions which tends to increase during the COVID-19 pandemic. Various factors increase the incidence of violence against women. This systematic literature review aims to identify the factors that influence the increase in incidence in women. Study literature on the Science Direct, Pubmed, Cinahl, EBSCO host and Cochrane Library databases with the PRISMA procedure and the Robvis bias assessment. A total of 5 articles were included in this systematic literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 11 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…The four main research questions were addressed in systematic reviews, including prevalence and incidence ( Abdo et al, 2020 ; Bayu, 2020 ; Cappa & Jijon, 2021 ; Javed & Mehmood, 2020 ; Kourti et al, 2021 ; Lausi et al, 2021 ; Marmor et al, 2021 ; McNeil et al, 2022 ; Pentaraki & Speake, 2020 ; Piquero et al, 2021 ; Rapp et al, 2021 ; Sánchez et al, 2020 ; Syibulhuda & Ediati, 2021 ; Viero et al, 2021 ), contributing factors ( Bayu, 2020 ; Javed & Mehmood, 2020 ; McNeil et al, 2022 ; Moreira & da Costa, 2020 ; Nasution & Fitriana, 2020 ; Pentaraki & Speake, 2020 ; Rapp et al, 2021 ; Sánchez et al, 2020 ; Syibulhuda & Ediati, 2021 ; Viero et al, 2021 ), mitigating policies and practices ( Kourti et al, 2021 ; Pentaraki & Speake, 2020 ; Sánchez et al, 2020 ; Su et al, 2021 ), and emerging issues and patterns of DV studies ( Cappa & Jijon, 2021 ; Javed & Mehmood, 2020 ; Kourti et al, 2021 ; Pentaraki & Speake, 2020 ; Viero et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The four main research questions were addressed in systematic reviews, including prevalence and incidence ( Abdo et al, 2020 ; Bayu, 2020 ; Cappa & Jijon, 2021 ; Javed & Mehmood, 2020 ; Kourti et al, 2021 ; Lausi et al, 2021 ; Marmor et al, 2021 ; McNeil et al, 2022 ; Pentaraki & Speake, 2020 ; Piquero et al, 2021 ; Rapp et al, 2021 ; Sánchez et al, 2020 ; Syibulhuda & Ediati, 2021 ; Viero et al, 2021 ), contributing factors ( Bayu, 2020 ; Javed & Mehmood, 2020 ; McNeil et al, 2022 ; Moreira & da Costa, 2020 ; Nasution & Fitriana, 2020 ; Pentaraki & Speake, 2020 ; Rapp et al, 2021 ; Sánchez et al, 2020 ; Syibulhuda & Ediati, 2021 ; Viero et al, 2021 ), mitigating policies and practices ( Kourti et al, 2021 ; Pentaraki & Speake, 2020 ; Sánchez et al, 2020 ; Su et al, 2021 ), and emerging issues and patterns of DV studies ( Cappa & Jijon, 2021 ; Javed & Mehmood, 2020 ; Kourti et al, 2021 ; Pentaraki & Speake, 2020 ; Viero et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In view of the fact that the review studies identified too many factors contributing to increased vulnerability to DV during the pandemic and the social distancing measures, the current systematic meta-review classified the factors based on an ecological framework, one of the most widely used theoretical models in DV research ( Kim, 2021 ). This classification strategy provides a better understanding of DV dynamics on different ecological system levels ( Nasution & Fitriana, 2020 ; Sánchez et al, 2020 ). Based on an ecological model of DV, we analyze it at four levels, namely ontogenetic (i.e., the individual’s development history), microsystem (i.e., the family unit), exosystem (i.e., the formal and informal social structures), and macrosystem (i.e., societal and cultural values and beliefs), and assumes that each of these domains contributes to risk and protective markers ( Kim & Merlo, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations